Resynchronization of estrus with progesterone and estrogen in previously inseminated beef cows - Medina-Britos, M.A.; Richardson, A.M.; Lamb, G.C.; Hensley, B.A.; Marple, T.J.; Stevenson, Jeffrey S.; Johnson, Sandra K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study was conducted in 609 beef cows to determine whether or not estrus might be resynchronized in previously inseminated beef cows to accommodate a second artificial insemination (AI) early in the breeding season. Previously inseminated cows were treated for 7 days with progesterone (via a previously used intravaginal progesterone-releasing insert [CIDR]) beginning 13 days after AI. In addition, injections of estrogen (estradiol benzoate [EB] or estradiol cypionate [ECP]) were given at insertion and removal of the CIDR insert. Rates of return to estrus and total pregnancy rates were increased after treatments with progesterone and estrogen compared with controls. No harm to pregnancies occurred in pregnant cows and a second AI period was facilitated by the end of the first 23 days of the breeding season.
Keywords: Beef; Cows; Resynchronization of estrus; Estrogen; Progesterone; Pregnancy rates